2002
DOI: 10.1016/s0736-5748(02)00011-4
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized NRG signaling and PDZ domain‐containing proteins in synapse structure and function

Abstract: The synapse-specific synthesis of the acetylcholine receptor (AChR) is mediated by multiple mechanisms including compartmentalized signaling induced by neuregulin (NRG). This paper presents evidence that NRG receptors--ErbB receptor tyrosine kinases interact with distinct PDZ domain-containing proteins that are localized at the neuromuscular junction (NMJ). ErbB4 associates with the PSD-95 (also known as SAP90)-family members including PSD-95, SAP97, and SAP102 whereas ErbB2 interacts with Erbin and PICK1. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 115 publications
(150 reference statements)
3
30
0
Order By: Relevance
“…Consistent with other investigators, we have demonstrated the expression and localization of ErbB2, ErbB3, and ErbB4 proteins in skeletal muscle and the enrichment of these receptors at the NMJ (2,14,15,25,40,48). A novel finding in our study is the increased expression of ErbB3 in the EDL, a predominantly fasttwitch, glycolytic muscle compared with the soleus, a predominantly slow-twitch, oxidative muscle.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other investigators, we have demonstrated the expression and localization of ErbB2, ErbB3, and ErbB4 proteins in skeletal muscle and the enrichment of these receptors at the NMJ (2,14,15,25,40,48). A novel finding in our study is the increased expression of ErbB3 in the EDL, a predominantly fasttwitch, glycolytic muscle compared with the soleus, a predominantly slow-twitch, oxidative muscle.…”
Section: Discussionsupporting
confidence: 92%
“…The demonstration that the SAPAPs are present at several types of excitatory synapses is consistent with the possibility that the SAPAP proteins are a general "core" component of all excitatory synapses. Moreover, PSD-95 family proteins have been found at neuronal cholinergic synapses (Conroy et al, 2003;Parker et al, 2003), and there have also been reports that PSD-95 and SAP97 are located at the neuromuscular junction (Rafael et al, 1998;Huang et al, 2002). Together, these observations suggest that there may be an entire "core" postsynaptic complex that is generally required for the structure and/or function of all excitatory synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in dlg-/-cause dramatic defects in the formation of septate junctions between epithelial cells [47,49] and of the larval NMJ [48] (see below). Four vertebrate homolog of DLG have been described, SAP90/PSD-95, SAP102, SAP97/hDlg and Chapsyn-110/PSD93 [5], all of which have been localized to CNS glutamatergic synapses (see [9,50]) as well as at cholinergic synapses of the CNS [51] and NMJ [52]. Of these, SAP97/hDlg is the most broadly expressed and is found in nearly every tissue and cell type.…”
Section: Members Of the Maguk Superfamilymentioning
confidence: 99%